Simulation-driven product development of cast components with allowance for process-induced material behaviour. Issue 1 (19th March 2020) - Jansson, J; Olofsson, J; Salomonsson, K
Abstract: This paper presents a methodology that can be used to consider local variations in thermomechanical and thermophysical material properties, residual stresses, and strength-differential effects in finite element analyses of cast components. The methodology is based on applying process simulations and structural analyses together with experimentally established, or already available literature data, in order to describe element-specific material variations. A cast-iron cylinder head was used in order to evaluate the influence of several simplifications that are commonly performed in computer aided engineering. It is shown that non-trivial errors of a potentially large magnitude are introduced by not considering residual stresses, compressive behaviour, temperature dependence, and process-induced material property variations. By providing design engineers with tools that allow them to consider the complex relationships between these aspects early in the development phase, cast components have the potential to be further optimized with respect to both weight and performance. Graphical Abstract: